A hyaluronic acid based lubricious coating for cardiovascular catheters. (November 2020) - Lin, Chengxiong; Wan, Hongping; Kaper, Hans Jan; Sharma, Prashant Kumar
Abstract: Hydrophilic lubricious coatings on the catheter surface reduce friction against the blood vessel wall but give rise to iatrogenic complication of particle release, embolization and thin blood vessel blockage leading to pulmonary infarction and stroke. Layer by layer deposited PLL (poly-l -lysine) and HA (hyaluronan) coating fills the urgent need of thinner lubricious coating which does not lead to release of large particles. The 8 layered PLL-HA coating was able to maintain low friction and prevent wear of endothelial glycocalyx layer (EGL). Wear and loss of EGL is a gradual process and occurred while sliding the blood vessel against bare catheter surface or 4 layered coating accompanied by epithelial cells damage and decrease in the number of nucleuses. Highlights: The catheter-blood vessel friction was mimicked using a reciprocating aorta-PU ball sliding system. There are clear difference in COF and frictional energy dissipation for different number of coating layers. Wear followed by loss of EGL and the changes on endothelial lining is a gradual process and depends on robustness of coating. Epithelial cells are gradually damaged and the number of nucleuses decrease with the sliding against coated surface.